Effect of structural design on traffic-induced building vibrations. (2017) - Persson, P.; Andersen, L.V.; Persson, K.; Bucinskas, P.
Abstract: Population growth and urbanization results in densified cities, where new buildings are being built closer to existing vibration sources, and new transportation systems are constructed closer to existing buildings. Potential disturbing vibrations are one issue to consider in planning urban environments and densification of cities. Vibrations can be annoying for humans but also for sensitive equipment in, for example, hospitals. In determining the risk for disturbing vibrations, the distance between the source and the receiver, the ground properties, and type and size of the building are governing factors. In the paper, a study is presented aiming at investigating the influence of various parameters of the building's structural design on vibration levels in the structure caused by ground surface loads, e.g. traffic. Parameters studied are related to the type of construction material (if it would be a light or heavy structure), and to the slab thickness. The study is limited to the structural response at frequencies near the first resonance frequency of the soil. The finite element method is employed for discretizing the building structure that is coupled to a semi-analytical model considering a layered ground.